Russian security and air power, 1992-2002 the development of Russian security thinking under Yeltsin and Putin and its consequences for the air forces - de Hass, Marcel (Cass series on Soviet (Russian) military theory and practice, 2004)
This book analyzes the security policy of the Russian Federation, internally as well as externally, on all levels of strategy. It describes military and political decision-making from Moscow's grand strategy to the use of a single fighter aircraft in Chechnya. In this analysis, Russia's air forces are used as a model for all services of the armed forces. The Chechen conflicts and NATO's security policy have been dominant factors in the development of Russia's security policy during the period 1992-2002. The use of air power in the Chechen conflicts is used here as a case study for testing political and military-strategic objectives. With regard to NATO's security policy, this study shows that the eastward enlargement of this alliance, as well as its use of force in Bosnia and Kosovo, have caused an increase in anti-Western tendencies in Russian security thinking.